Imaging of Mouse Brain Fixated in Ethanol in Micro-CT - Mrzílková, Jana; Patzelt, Matěj; Gallina, Pasquale; Wurst, Zdeněk; Šeremeta, Martin; Dudák, Jan; Krejčí, František; Žemlička, Jan; Musil, Vladimír; Karch, Jakub; Rosina, Jozef; Zach, Petr (BioMed research international, 2019)
Micro-CT imaging is a well-established morphological method for the visualization of animal models. We used ethanol fixation of the mouse brains to perform high-resolution micro-CT scans showing in great details brain grey and white matters. It was possible to identify more than 50 neuroanatomical structures on the 5 selected coronal sections. Among white matter structures, we identified fornix, medial lemniscus, crossed tectospinal pathway, mammillothalamic tract, and the sensory root of the trigeminal ganglion. Among grey matter structures, we identified basal nuclei, habenular complex, thalamic nuclei, amygdala, subparts of hippocampal formation, superior colliculi, Edinger-Westphal nucleus, and others. We suggest that micro-CT of the mouse brain could be used for neurohistological lesions evaluation as an alternative to classical neurohistology because it does not destroy brain tissue.
Keywords: Ethanol; Animals; Tissue Fixation; mužské pohlaví; zvířata; rentgenová mikrotomografie; Male; Mice; X-Ray Microtomography; Brain; ethanol; fixace tkání; mozek; myši